Clinical observation of Baduanjin exercise on bed in relief of constipation among patients with acute myocardial infarction (床上八段锦改善急性心肌梗死患者便秘的效果观察) - LI Fengyan (李丰艳); GONG Zhencui (宫振翠); SHI Yu (时玉) (中西医结合护理)
Objective To observe the effect of Baduanjin exercise on bed (abdominal acupoint massage with Shuangtong Qihai technique) in relief of constipation among patients with acute myocardial infarction(AMI). Methods Totally 80 AMI patients with constipation were randomly divided into control group and intervention group, with 40 cases in each group. All patients received routine care and dietary instruction. Routine abdominal massage was carried out in the control group, while abdominal acupoint massage with Shuangtong Qihai technique of Baduanjin exercise was performed in the intervention group. To assess the constipation symptom and bowel sounds before intervention, 3 days and 7 days after intervention, and to compare the effect of intervention between two groups. Results The total score of constipation symptom assessment in the intervention group was lower than that in the control group at 3 days and 7 days after intervention (P＜0. 01). the frequency of bowel sounds in the intervention group was higher than that in the control group at 3 days and 7 days after intervention(P＜0. 01). The overall effective rate in the intervention group was higher than that in the control group (87. 50% vs, 67. 50%, P＜0. 05). Conclusion The abdominal acupoint massage with Shuangtong Qihai technique of Baduanjin exercise is potentially effective in in relief of constipation among AMI patients. (目的 观察床上八段锦中双通气海手法腹部穴位按摩改善急性心肌梗死患者便秘的效果。方法 选取科室收治的急性心肌梗死患者80例为研究对象, 均伴有不同程度便秘。随机分为对照组和干预组, 各40例。2组均给予常规护理和饮食指导, 对照组给予常规腹部按摩, 干预组采用床上八段锦中双通气海手法进行腹部穴位按摩。干预前、干预后3 d、7 d评估患者便秘症状总积分、肠鸣音等指标, 评价临床疗效。结果 干预后3 d和干预后7 d天, 干预组便秘症状总积分低于对照组, 肠鸣音次数高于对照组, 差异有统计学意义(P＜0. 01)。干预组总有效率87. 50%(35/40), 高于对照组的67. 50%(27/40), 差异有统计学意义(P＜0. 05)。结论 运用床上八段锦中双通气海手法进行自主腹部穴位按摩能, 有效改善急性心肌梗死患者便秘。)